2018
DOI: 10.1111/php.12884
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and Photophysics of Shinorine Dimethyl Ester

Abstract: The photostability and photophysical properties of the dimethyl ester of the mycosporine-like amino acid shinorine have been experimentally evaluated in aqueous solution and in the presence of direct micelles prepared with a cationic or an anionic detergent, respectively. In comparison with shinorine, the ester molecule increases the photostability, the fluorescence quantum yield and the fluorescence lifetime in water as well as in the micellar solutions. The effects are more pronounced in sodium dodecyl sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Given the continuing increase in skin cancer cases and recent concerns raised over current sunscreen filters such as phototoxicity and photdegradation, 9,10,1315,6668 unravelling photoprotection mechanisms through an intrinsic understanding of the photochemistry of both nature-based (and inspired) and artificial sunscreen filters continues to grow as a field of research. 16,27,69 Studies on exploring the synthesis and isolation of MAAs in nature provides complementary aspects of this research. 7,70,71 That being said, more work is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Given the continuing increase in skin cancer cases and recent concerns raised over current sunscreen filters such as phototoxicity and photdegradation, 9,10,1315,6668 unravelling photoprotection mechanisms through an intrinsic understanding of the photochemistry of both nature-based (and inspired) and artificial sunscreen filters continues to grow as a field of research. 16,27,69 Studies on exploring the synthesis and isolation of MAAs in nature provides complementary aspects of this research. 7,70,71 That being said, more work is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Orallo et al [ 136 , 137 ] have performed studies on the MAAs shinorine, porphyra-334 and shinorine dimethyl ester in micellar solutions to elucidate the photochemistry and photophysics in a closer-to-real sunscreen formulation environment. They found that the fluorescence quantum yield and lifetime were increased in micelle solutions compared to aqueous solutions; however, the main deactivation process remained via non-radiative decay.…”
Section: Case Studiesmentioning
confidence: 99%
“…The authors attributed both properties to the electrostatic interactions between MAAs and micelles which hinder molecular movements. Overall, Orallo et al [ 136 , 137 ] demonstrated that MAAs in micellar solutions which mimic a closer-to-real environment, with regards to sunscreen formulation, still perform as efficient UV filters which is promising for commercial applications. However, the electrostatic interactions which influence the decay mechanisms must be taken into account.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation